The discovery of angiotensin‐converting enzyme 2 and its role in acute lung injury in mice - Imai, Yumiko (Exp Physiol, 2008)
During several months of 2002, severe acute respiratory syndrome (SARS) caused by SARS‐coronavirus (SARS‐CoV) spread rapidly from China throughout the world, causing more than 800 deaths due to the development of acute respiratory distress syndrome (ARDS), which is the severe form of acute lung injury (ALI). Interestingly, a novel homologue of angiotensin‐converting enzyme, termed angiotensin‐converting enzyme 2 (ACE2), has been identified as a receptor for SARS‐CoV. Angiotensin‐converting enzyme and ACE2 share homology in their catalytic domain and provide different key functions in the renin–angiotensin system (RAS). Angiotensin‐converting enzyme cleaves angiotensin I to generate angiotensin II, which is a key effector peptide of the system and exerts multiple biological functions, whereas ACE2 reduces angiotensin II levels. Importantly, our recent studies using ACE2 knockout mice have demonstrated that ACE2 protects murine lungs from ARDS. Furthermore, SARS‐CoV infections and the Spike protein of the SARS‐CoV reduce ACE2 expression. Notably, injection of SARS‐CoV Spike into mice worsens acute lung failure in vivo, which can be attenuated by blocking the renin–angiotensin pathway, suggesting that the activation of the pulmonary RAS influences the pathogenesis of ALI/ARDS and SARS.